Analysis of Effect of Sound Frequency Against System Open Close Stomata of Rice Plant of Logawa Variety - Kuni Nadliroh; Chomsin S. Widodo; Didik R. Santoso (Natural B, Journal of Health and Environmental Sciences, 2015)
This study aimed to determine the effect of sound waves to open the closed stomata rice plants in sonic bloom technology, the frequency used for rice crops, as well as help the intensification of agriculture. This study was conducted on rice types Logawa, where rice plants used are rice plants ready for planting. Ready for planting rice plants treated without wave, 10 Hz, 4 kHz, 7 kHz, 30kHz. Parameters measured were wide rice plant stomata. The results showed that the rice plants have stomata greatest width occurs when the plant is given 4 kHz frequency sound waves, the waves at 06.00 - 09.00.